2017
DOI: 10.1186/s13567-017-0437-2
|View full text |Cite
|
Sign up to set email alerts
|

Innate immune responses induced by the saponin adjuvant Matrix-M in specific pathogen free pigs

Abstract: Saponin-based adjuvants have been widely used to enhance humoral and cellular immune responses in many species, but their mode of action is not fully understood. A characterization of the porcine transcriptional response to Matrix-M was performed in vitro using lymphocytes, monocytes or monocyte-derived dendritic cells (MoDCs) and in vivo. The effect of Matrix-M was also evaluated in specific pathogen free (SPF) pigs exposed to conventionally reared pigs. The pro-inflammatory cytokine genes IL1B and CXCL8 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 61 publications
(62 reference statements)
0
20
0
Order By: Relevance
“…The upregulation of Mx gene expression in the liver and spleen tissues along with an improvement of IFN‐α activity in the serum indicated that BSA ISCOMs induced an antiviral‐associated innate immune response in large yellow croaker 30 days after feeding. Similarly, Ahlberg et al () showed that Matrix‐ M (ISCOMs without antigens or protein) induced IFN‐α expression in pigs.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The upregulation of Mx gene expression in the liver and spleen tissues along with an improvement of IFN‐α activity in the serum indicated that BSA ISCOMs induced an antiviral‐associated innate immune response in large yellow croaker 30 days after feeding. Similarly, Ahlberg et al () showed that Matrix‐ M (ISCOMs without antigens or protein) induced IFN‐α expression in pigs.…”
Section: Discussionmentioning
confidence: 92%
“…It is confirmed that ISCOMs are highly effective adjuvant systems capable of inducing a broad range of immune responses, including balanced Th1 and Th2 CD4(+) T‐cell priming, cytotoxic T lymphocyte cell responses, specific serum antibodies and a strong mucosal immunoglobin A (IgA) response (Anja et al, ; Morein, Hu, & Abusugra, ). In addition, many studies showed that ISCOMs enhanced innate immune responses in mammals, such as inducing the expression of interleukin (IL)‐1B, chemokine ligand 8 (CXCL8), IL‐12B, IL‐17A, interferon (IFN)‐α and Toll‐like receptor 2 (TLR2) (Ahlberg et al, ; Ahlberg, Lovgren Bengtsson, Wallgren, & Fossum, ; Fossum et al, ). Hence, ISCOMs have a broad spectrum of immune responses and can be administered through the mucosal membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Tonsil samples were obtained from pigs aged 9–11 weeks being used as untreated control animals in a study on a saponin-based adjuvant [ 12 ]. The experiment was approved by the Uppsala Ethical Committee on Animal Experiments (Reg.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, developing a vaccine targeting RBD can inhibit viral attachment hence, fusion. (54,55). This adjuvant, when compared with other adjuvants like Alum, AS03, and FCA, is a more potent alternative (56).…”
Section: Structure and Life Cyclementioning
confidence: 98%